ANALISIS HARGA DAN KUALITAS PRODUK USAHA TAHU TERHADAP KEPUASAN PELANGGAN DI DESA KOTO TINGGI - Nurfauziah Nurfauziah; Heffi Christya Rahayu; Ratna Dewi (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the influence of price and product quality of tofu businesses on customer satisfaction in Koto Tinggi Village. The phenomenon found in the field shows that the price of tofu is not commensurate with the quality of tofu products that often change, such as texture, taste, and aroma of tofu, which often affects customer satisfaction. Customer satisfaction is an important factor in maintaining business continuity. The research method used in this study is quantitative descriptive with multiple linear regression analysis techniques assisted by SPSS software version 21. The population in this study were all consumers of tofu businesses in Koto Tinggi Village with a sample size of 110 respondents. Sampling was carried out using a purposive sampling technique where the sample was selected based on criteria determined by the researcher. Data collection was carried out through observation, interviews, and questionnaires. The collected data were then analyzed to determine the effect of each independent variable on the dependent variable. The results of the study indicate that price has a positive effect on customer satisfaction of tofu businesses in Koto Tinggi Village. The variable of product quality also has a positive effect on customer satisfaction of tofu businesses in Koto Tinggi Village. Simultaneously, price and product quality influence customer satisfaction of tofu businesses in Koto Tinggi Village.